Remote physical education during the coronavirus pandemic. A discourse analysis of how students are positioned on Padlet webpages - Daniel Rode; Benjamin Zander (Bern Open Publishing, 2023)
During the coronavirus pandemic, physical education (PE) in schools was forced into remote forms of teaching and learning, leading to a surge in the use of digital technologies and online resources. In a larger project, we identified webpages created by PE teachers on the site Padlet.com as an important hub for the remote delivering of German-speaking PE during the pandemic. In this paper, we follow a poststructuralist perspective to investigate how students are positioned as subjects of pandemic PE through the discursive practices articulated on these webpages. Our discourse analysis of a sample of 14 webpages with a combined number of 755 posts reveals one largely uncontested discursive construction that positions students as (i) doing something during lockdown, (ii) using suggestions individually and self-responsibly, (iii) exercising, performing, fit, and (iv) predominantly able bodied, sporty, stereotypically gendered, and white. We critically discuss the narrow possibilities of becoming intelligible as an appropriate subject of pandemic PE afforded by these positionings in the context of foregoing scholarship. Concluding, we argue that even - or especially - when PE has been returning to its traditional co-present form, exploring how PE is socially constructed, how students are positioned, and which forms of subjectivity are privileged/marginalized in emerging PE-related online cultures is a crucial task for sport pedagogical research and practice.